Analisis Epigalokatekin Galat Dalam Minuman Teh Hijau Siap Saji - Kurniadi, Maryati; Leswara, Nelly D.; Rinayanti, Yola (Majalah Ilmu Kefarmasian, 2007)
Epigallocatechin gallat (EGCg) is a polyphenol constituent in tea that has antioxidant effect. The purpose of this research was to identify and examine qualitative and quantitative EGCg in green tea preparations which were stored in different condition, that was in a refrigerator and in an open air. The results showed that all samples containing EGCg. The examination of EGCg concentration in the sample was done by thin layer chromatography densitometric method using cellulose plate. N-propanol - acetic acid - water (1:1:5) was the selected eluent. Linear regression equation from calibration curve was y = -1204.071 + 7.495 x, with correlation factor (r) = 0.99911. EGCg concentration from sample that stored in refrigerator sample number one was 0.00293% w/v, sample number two was 0.00298% w/v, and sample number three was 0.00328% w/v. EGCg concentration from sample that stored in open air was lower than LOD.